Pochwała wielkiej księżnej włodzimierskiej Marii. Edycja i przekład nieznanego zabytku literatury staroruskiej. - Brzozowska, Zofia (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
This paper is devoted to one particular historical source: the praise of the Grand Princess of Vladimir, Maria Shvarnovna, the first wife of Vsevolod III the Big Nest. The text can be found in the Chronicle of Trinity Monastery, compiled in Moscow around 1408. The monument has not survived to our days and we have only a reconstruction of the text by Priselkov. The publication is divided into three parts. The introduction gives background information on Maria Shvarnovna and the text. Secondly, the Old-Church-Slavonic/Old Russian original edition is included. The last and the longest part of the article contains the complete Polish translation. Bible citations and all additional historical information and references can be found in the footnotes.